2015
DOI: 10.3945/ajcn.114.089581
|View full text |Cite
|
Sign up to set email alerts
|

Fiber intake and risk of subsequent prostate cancer in Japanese men

Abstract: Dietary fiber is inversely associated with advanced prostate cancer detected by subjective symptoms even among populations with relatively low intake, such as Japanese. These results suggest that a very low intake of dietary fiber is associated with an increased risk of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Although these inverse associations have been attributed to the high dietary fiber content of mature beans (63), the association between dietary fiber intake and CaP has been inconsistent (6468). Additionally, many fruits and vegetables have high fiber content, and yet we did not observe any inverse associations for fruit and vegetable intake.…”
Section: Discussionmentioning
confidence: 99%
“…Although these inverse associations have been attributed to the high dietary fiber content of mature beans (63), the association between dietary fiber intake and CaP has been inconsistent (6468). Additionally, many fruits and vegetables have high fiber content, and yet we did not observe any inverse associations for fruit and vegetable intake.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, insoluble fiber consumption was significantly associated with a decreased risk of EHBDC. A protective effect of fiber on colorectal cancer was judged as “conclusive,” and the protective effect of insoluble fiber on prostate cancer was observed . There are multiple potential mechanisms for a cancer‐protective effect of fiber such as improving insulin‐resistance, decreasing IGF activity, producing an anti‐inflammatory effect through the production of butylate, and optimizing the colonic micro‐biota reinforcing the intestinal barrier .…”
Section: Discussionmentioning
confidence: 99%
“…It has been supposed that dietary fiber might decrease risk of prostate cancer by improving insulin sensitivity and decrease bioactivity of Insulin-like growth factor-1 IGF-1 (Barnard et al, 2002). Previous cohort and case-control studies have demonstrated that total, insoluble, soluble and legume fiber are inversely associated with prostate cancer risk (Tabung et al, 2012;Deschasaux et al, 2014;Sawada et al, 2014). Similarly, the ''plant source" pattern (loaded heavily on potassium, Vitamin K, total folate, beta-carotene and lutein) was negatively associated with risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%